Nutritional interventions in adult fibrostenotic Crohn’s disease: A systematic review - Cooper, Jared L.; Rosentreter, Ryan E.; Filyk, Alexis; Premji, Zahra A.; Shen, Hua; Ingram, Richard; Kaplan, Gilaad G.; Ma, Christopher; Novak, Kerri; Panaccione, Remo; Seow, Cynthia H.; Rieder, Florian; et al. (Frontiers in Nutrition, 2023)
Background: Management of Crohn’s Disease (CD) using dietary interventions has become an area of increased research interest. There is a lack of specific research exploring if diet and nutrition interventions are beneficial in patients with strictures, as current dietary recommendations in fibrostenotic CD are often based on clinical judgement. The aim of this systematic review was to assess the impact of dietary interventions in fibrostenotic CD on medical and surgical outcomes. Methods: A systematic search of MEDLINE (Ovid), EMBASE (Ovid), CINAHL (EBSCO), and Cochrane Central Register of Controlled Trials (Ovid) was conducted. Studies reporting dietary interventions or nutritional factors in fibrostenotic CD were included. Outcomes for studies assessing dietary interventions such as enteral nutrition were evaluated as changes in 1) CD symptoms (CD Activity Index), 2) stricture parameters on diagnostic imaging, and 3) rates of surgical or medical intervention following dietary interventions. Results: Five studies were included in this review. Three studies assessed exclusive enteral nutrition (EEN), one evaluated total parenteral nutrition (TPN), and one studied a liquid diet. All included studies evaluated symptoms as an outcome, while diagnostic imaging parameters and surgical outcomes in the studies were either absent or too heterogeneous to appraise improvement post dietary intervention. Included EEN studies displayed similar efficacy, with approximately 60% of patients having symptom improvement. The included TPN study also reported 75% of patients with symptom improvement, while the liquid diet did not. Conclusion: Exclusive enteral nutrition and total parental nutrition may provide benefit for use as a dietary intervention for fibrostenotic CD. There remains a need for high-quality controlled trials which utilize standardized definitions of strictures.